A REVIEW ON SUSTAINABLE CONSTRUCTION REGULATIONS IN DEVELOPED COUNTRIES: KEY LESSONS AND INSIGHTS FOR INDONESIA - Erik Wahyu Palguna; Diajeng Sekar Shaliha; Iola Abi Gail; Indra Rio Saputro; Via Azizul Saputri Khalifah (Fakultas Teknik Universitas Pasifik Morotai, 2026)
The construction sector is a major contributor to global energy consumption, greenhouse gas emissions, and resource depletion, making sustainable construction regulations an urgent policy priority. This systematic literature review examines regulatory frameworks, policy instruments, and implementation experiences from developed countries including the United States, Japan, the United Kingdom, and European countries and synthesizes key lessons applicable to Indonesia. Following Mayring’s process model, 50 peer reviewed articles were selected through a rigorous four-stage screening protocol and analyzed using qualitative content analysis. The findings reveal that effective sustainable construction governance in developed countries relies on mandatory building codes, green building certification programs (LEED and BREEAM), life cycle assessment requirements, financial incentives such as tax credits and subsidies, and alignment with broader circular economy and carbon neutrality objectives. Conversely, Indonesia and comparable developing countries continue to face persistent barriers including weak law enforcement, prohibitive upfront costs, fragmented governance, limited stakeholder awareness, and insufficient financial incentives. The study concludes that direct transplantation of foreign regulatory models is impractical; instead, context-sensitive adaptation that accounts for local economic realities and institutional capacities is essential. Practical recommendations are offered for Indonesian policymakers and construction practitioners to strengthen legal frameworks, expand incentive mechanisms, improve enforcement, and invest in stakeholder education.